Uji Daya Hambat Ekstrak NADES Bunga Telang (Clitoria ternatea) terhadap Bakteri Staphylococcus aureus: Inhibitory Test of NADES Extract of Butterfly Pea Flower (Clitoria ternatea) against Staphylococcus aureus Bacteria - Siti Juariah; Fitria Desrita Sari; Rosa Devitria; Eli Yusrita; Susi Endrini (Elektriese: Jurnal Sains dan Teknologi Elektro, 2026)
Butterfly pea (Clitoria ternatea), also known as butterfly pea, is a climbing plant from the Fabaceae family that has great potential as a source of natural antibacterials. This plant contains various bioactive compounds, including alkaloids, tannins, saponins, anthocyanins, and phenolics, which contribute to its antibacterial activity. This study aims to evaluate the inhibitory effect of butterfly pea flower extract on Staphylococcus aureus growth and to analyze the relationship between extract concentration and antibacterial activity. The research method used a diffusion test with treatment variations in extract concentration (25%, 50%, and 75%), as well as a positive control (chloramphenicol) and a negative control (Aquadest. The diameter of inhibition (DDH) was measured with a caliper to ensure accuracy. In addition, phytochemical screening was performed to identify the active compounds in the extract. The results showed the presence of flavonoids, tannins, alkaloids, phenols, and saponins, all of which act as antibacterial agents. The antibacterial test results showed that butterfly pea flower extract significantly inhibited the growth of Staphylococcus aureus, with a highly significant difference in inhibitory activity across concentrations. The highest antibacterial activity was observed at 75% concentration, with an average DDH of 26.53 mm, placing it in the very strong inhibitory power category. Increasing the extract concentration is consistent with increased antibacterial effectiveness. Butterfly pea flower extract has the potential to be developed into an effective, safe, natural antibacterial alternative.